9/11, Hyperreality, and the Global Body Politic: Frédéric Beigbeder’s Windows on the World - Jenn Brandt (Studies in 20th & 21st Century Literature, 2015)
This essay argues that the success of Frédéric Beigbeder's Windows on the World is due to Beigbeder's use of the seemingly contradictory genres of autofiction and hyperrealism in the depiction of the terrorist attacks of September 11, 2001. By positioning himself in the text alongside his fictionalized American counterpoint, Beigbeder configures 9/11 as a lived-body experience that models the ways in which the post-9/11 subject was formed within specific political, cultural, and national conditions. The effect of the novel’s hyperrealism is such that Beigbeder simultaneously posits and deconstructs the notion of national identity within the greater contexts of postmodernism and globalization.
Keywords: autofiction; 9/11; transnationalism; globalization; hyperrealism; contemporary French literature; Frédéric Beigbeder; Windows on the World